THE INFLUENCE OF COMMUNICATION AND ORGANIZATIONAL CULTURE ON JOB SATISFACTION AT PT. MITRA AGUNG - Nasution, Muhammad Ilham; Syahlina, Maya; Hou, Amin; Tambunan, Debora; Chaniago, Sabaruddin (ZILLZELL MEDIA PRIMA, 2023)
This study supposed to analyze the influence of communication and organizational culture on job satisfaction. Population in this study employees at PT. Mitra Agung Swastika, with a total of 80 respondents. Data collection methods using interviews and questionnaires. Data analysis techniques using multiple regression. The results showed that communication has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, communication and organizational culture has a positive and significant effect on job satisfaction, and the coefficient of determination of the variation of the dependent variable is communication and organizational culture has a contribution to job satisfaction at PT. The Grand counterpart of the Swastika in the category of strong.